HYDATID DISEASE INVOLVING CERVICAL SOFT TISSUES: CLINICAL CASE - A. S. Aladin; E. V. Kutubulatova; V. A. Semenov; G. A. Krokhalev; K. S. Shumilina (Опухоли головы и шеи, 2015)
Neck cysts are rather commonly encountered in the practice of a surgeon, including an oncologist, who treats diseases of the head and neck. At the same time there are rare involvements of the organs and soft tissues of the neck. In particular, echinococcosis of neck soft tissues is an unusual site for hydatid cyst. Accounts of this involvement are found only as single communications in the literature. The presented case of hydatid cyst illustrates a variety of neck abnormalities.